The dissociation behaviour of a singly and doubly charged (cationised) aza-crown ether/metalloporphyrin-conjugate: Metal-induced reactivity and Coulomb explosions Dedication: In memory of Prof. Detlef Schröder. - Li, Jing; Dürr, Katharina L.; von Gernler, Marc; Jux, Norbert; Ivanovic-Burmazovic, Ivana; Drewello, Thomas (International Journal of Mass Spectrometry, 2013)
Fe(III) and Mn(III) complexes of an aza-crown ether/porphyrin conjugate, 5-N-(4-aza-18-crown-6)methyl-5,10,15 ,20-tetra-tert-butyl-5-methyl-5,10,15,20- tetraphenylporphyrin, with Cl and Br as respective counter ions, are studied by electrospray ionisation (ESI)-mass spectrometry (MS). Fragmentation pathways are established by MS and MS collision-induced dissociation (CID) experiments performed with a quadrupole ion trap (QIT) and energy-dependent CID is studied with a quadrupole/time-of-flight (q-ToF) instrument. Singly charged ions are produced by selective protonation, sodiation or potassiation of the crown ether moiety, and dications possess one additional charge on the halide-released porphyrin metal cation. Singly charged parent ions undergo a two-step decay. Firstly, an "ion pair" is lost, composed of the cationic charge carrier of the crown ether and the anionic counter ion at the porphyrin. Secondly, the intact crown ether is released. The threshold of this process is dependent on the nature of the central porphyrin metal, with Fe(III) dramatically facilitating the reaction. The dications undergo two different Coulomb explosions: crown/porphyrin-fission and cation loss from the crown ether, the ratio of which is dependent on the affinity of the cation to the crown ether. © 2013 Elsevier B.V. All rights reserved.